Mobile phone addiction and sleep quality among Chinese adolescents: A moderated mediation model. (July 2017) - Liu, Qing-Qi; Zhou, Zong-Kui; Yang, Xiu-Juan; Kong, Fan-Chang; Niu, Geng-Feng; Fan, Cui-Ying
Abstract: Research has revealed that mobile phone addiction was a risk factor for poor sleep quality, however, little is known about the underlying mechanisms that may mediate or moderate this association. This study examined the mediating role of rumination and moderating role of mindfulness in the association between mobile phone addiction and sleep quality. A sample of 1196 Chinese adolescents was recruited to complete measures of mobile phone addiction, sleep quality, rumination and mindfulness. Results showed that rumination partially mediated the relationship between mobile phone addiction and sleep quality. Besides, both the effect of mobile phone addiction on sleep quality and the mediating effect of rumination were moderated by mindfulness, and both of the two effects were stronger for individuals with lower mindfulness. The present study can advance our understanding of how and when mobile phone addiction leads to poor sleep quality. Limitations and implications of this study are discussed. Highlights: Mobile phone addiction was significantly correlated with sleep quality in adolescents. Rumination partially mediated the relation between mobile phone addiction and sleep quality. Mindfulness moderated the relation between mobile phone addiction and sleep quality. Mindfulness moderated the mediating role of rumination in the relation between mobile phone addiction and sleep quality.